Pemenuhan Kuota Hak Pekerja Penyandang Disabilitas di Kota Yogyakarta - Lalu Bintang Wahyu Putra (Program Studi Pembangunan Masyarakat Desa (D3), 2025)
This study examines the implementation of the fulfillment of the quota for disabled workers in the city of Yogyakarta, as regulated in national and regional regulations. This study uses a descriptive qualitative approach, collecting data through interviews, observations, and literature studies with triangulation techniques to maintain validity. The results of the study indicate that even though regulations and institutions such as the Disability Service Unit (ULD) for Employment have been available, the fulfillment of the quota for the rights of disabled workers is still not optimal. Government agencies and BUMD have not implemented the mandate of a 2 percent quota for disabled workers. Meanwhile, on the other hand, the private sector has shown better progress in absorbing disabled workers. The low participation of disabilities in the formal sector is due to minimal access to information, lack of relevant training, and strong discriminatory practices in the recruitment and job placement process